2012
DOI: 10.1016/j.apmr.2012.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Activity Pacing, Avoidance, Endurance, and Associations With Patient Functioning in Chronic Pain: A Systematic Review and Meta-Analysis

Abstract: Although causation cannot be determined, results of this study suggest that both avoidance of activity and overactivity are associated with poorer patient outcomes. Unexpected results relating to pacing may reflect either the ineffectiveness of pacing if not used to gradually increase an individual's activity level or the notion that individuals with better psychological functioning but more pain and disability are more inclined to pace activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
160
4
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(199 citation statements)
references
References 83 publications
20
160
4
10
Order By: Relevance
“…Whether pacing is indeed helpful, though, remains unclear [16]. A recent meta-analysis found weak correlations with pain and physical disability, but also with better psychological functioning [3]. This meta-analysis, however, included studies in which breaks may have also been pain-contingent.…”
Section: Discussionmentioning
confidence: 99%
“…Whether pacing is indeed helpful, though, remains unclear [16]. A recent meta-analysis found weak correlations with pain and physical disability, but also with better psychological functioning [3]. This meta-analysis, however, included studies in which breaks may have also been pain-contingent.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively controlled and simplified situation of cycling a time trial against a competing opponent while monitoring pacing behavior can provide new insights in how exercisers regulate their exercise intensity, supporting the suggestion that not only internal, but also external information is incorporated in the decision at what intensity to exercise [2]. A better understanding of the decision-making process involved in pacing behavior could even contribute to our general understanding of the way people pace their activities in daily life or how exercise intensity is regulated when achieving demanding goals in a rehabilitation context [4].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who are habitually overactive identify with being hardworking and successful, 7 but high levels of overactivity have been quantitatively linked to more self-reported physical disability, perceived difficulties participating in certain daily activities, and poorer psychological functioning. 3,5 As many of the participants in this study had been experiencing pain for an extended period of time, the observed association may be more reflective of habitually overactive individuals being less likely to cease opioid therapy after its initiation. Qualitative findings by Andrews et al 7 provide support for this idea as some habitually overactive participants in their study reported reliance on opioid medication to function effectively and inability to reduce opioid medication usage despite receiving encouragement, and guidance on how to do so, during a multidisciplinary pain management program.…”
Section: Discussionmentioning
confidence: 87%
“…3,15,35 Some authors have argued that self-report measures may be more reflective of paincontingent behaviour than quota-contingent behaviour as items from existing measures do not provide a specific reason why, or context in which, an individual is using a pacing strategy. 3,37,38 Other authors have suggested that activity pacing, as a stand-alone treatment, encourages adaptation to an illness, as opposed to ameliorating an illness (which is the goal of a combined operantbased pacing and graded activity program). 54 Because of this, the pacing subscale was not used in this study.…”
Section: Self-reported Habitual Approach To Activity Engagementmentioning
confidence: 98%